Analisis Matriks Boston Consulting Group (BCG) untuk Memenangkan Strategi Organisasi (Studi Kasus Perguruan Tinggi Di Kopertis Wilayah III â DKI Jakarta) - Sarjono, Haryadi; Achmad Kuncoro, Engkos (Binus Business Review, 2013)
This research intends to know position of market growth in higher education, especially Sekolah Tinggi, based on market share, using BCG metrics. Unit analysis is all private higher educations in Kopertis III â DKI Jakarta, consisting of University, Sekolah Tinggi, Institute, and Academics. The object of analysis is the numberof new student admission. Method of data collection in this paper is field research including observation and literature research method. The secondary data used in this study is data from Kopertis region III. Based on the results of the study, it is obtained Sekolah Tinggi for the academic year 2008 and 2009 is in quadrant III (Cash Cow).